Socialization of Ship Fire Prevention For Fishermen In East Sapa Village - Fajar Sutopo; Jeihn Novita C Budiman; Aliong Silalahi; Kriswanto Kriswanto; Azhar Ariansyah Ansar (Lembaga Pengembangan Kinerja Dosen, 2024)
Shipping activities, especially for fishermen, have significant risks. In addition to the unexpected challenges of nature, one of the serious threats that is often overlooked is the risk of ship fires. Fires can occur due to a variety of factors, such as mechanical failures, fuel leaks, or other accidents. The purpose of this study is to find out the socialization of ship fire prevention for fishermen in East Sapa village. The research method used in the socialization of ship fire prevention is a qualitative method. This approach was chosen to deeply understand the knowledge, attitudes, and skills of fishermen related to fire prevention and safety at sea. The results of this study show that community service activities carried out by the North Sulawesi Shipping Polytechnic in collaboration with the East Sapa Village government have succeeded in achieving their goals in providing education and practical skills to the fishing community. The program, which combines interactive counseling and training, has successfully increased the fishermen's knowledge and awareness of various important aspects of their work, including boat maintenance, life safety at sea, and fire prevention.